Planowanie przestrzenne niezbędnym elementem skutecznej strategii rekultywacyjnej = Spatial planning as essential part of the efficient reclamation strategy - Greinert, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Reclamation of demoted and devastated terrains is the combined activity, leaning about picture their future utilization. It?s links the question of protection and formation of habitat with spatial planning. Nowadays a serious problem exists in reclamation workings placing in spatial planning. Very clear are shortages in legal linking between plans and strateg-ic documents. The reclamation of terrains can be effective one and only in the conditions of planning stability. It has a special meaning at present time in discussion about change of Spatial planning and managing act and related legal acts.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); rekultywacja terenów; planowanie przestrzenne; areas reclamation; spatial planning